Consensus statements on vaccination in patients with haemophilia—Results from the Italian haemophilia and vaccinations (HEVA) project. Issue 4 (16th April 2019) - Santagostino, Elena; Riva, Agostino; Cesaro, Simone; Esposito, Susanna; Matino, Davide; Mazzucchelli, Renata Ilde; Molinari, Angelo Claudio; Mura, Rosamaria; Notarangelo, Lucia Dora; Tagliaferri, Annarita; Di Minno, Giovanni; Clerici, Mario; et al.
Abstract : Vaccination against communicable diseases is crucial for disease prevention, but this practice poses challenges to healthcare professionals in patients with haemophilia. Poor knowledge of the vaccination requirements for these patients and safety concerns often result in vaccination delay or avoidance. In order to address this issue, a panel of 11 Italian haemophilia and immunization experts conducted a Delphi consensus process to identify the main concerns regarding the safe use of vaccines in patients with haemophilia. The consensus was based on a literature search of the available evidence, which was used by the experts to design 27 consensus statements. A group of clinicians then rated these statements using the 5‐point Likert‐type scale (1 = strongly disagree; 5 = strongly agree). The main issues identified by the expert panel included vaccination schedule for haemophilic patients; protocol and optimal route of vaccine administration; vaccination of haemophilic patients with antibodies inhibiting coagulation factor VIII (inhibitors); and vaccination and risk of inhibitor development. This manuscript discusses these controversial areas in detail supported by the available literature evidence and provides evidence‐ and consensus‐based recommendations. Overall, participants agreed on most statements, except those addressing the potential role of vaccination in inhibitor formation. Participants agreed that patients with haemophilia should receive vaccinations according to the institutional schedule for individuals without bleeding disorders; however, vaccination of patients with haemophilia requires comprehensive planning, taking into account disease severity, type and route of vaccination, and bleeding risk. Data also suggest vaccination timing does not need to take into consideration when the patient received factor VIII replacement.